Theological Impact of Marriage for Religious Minority Families in Bali and Makassar - Abbas, Nurlaelah; Mahmuddin, Mahmuddin; A. Samad, Sri Astuti; Samad, Munawwarah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study seeks to explore the challenges faced by the minority group of Muslim families in Bali and Hindu families in Makassar in practicing their religious beliefs, highlighting the insufficient facilities and community support available to them. They need to put in more effort to uphold the practice of worship, holidays, and fasting. Marriage significantly influences numerous facets of life, encompassing social, emotional, financial, and legal dimensions. The research method employed is qualitative, analyzed through a theological lens. Qualitative analysis techniques rely on qualitative data, which consists of words and is essential for drawing thorough and high-quality conclusions. Data were gathered through comprehensive interviews and a thorough analysis of the literature. The study's findings indicate that for Muslim families in Bali, interactions significantly influence theological aspects related to worship, culture, customs, and social interactions. In Bali, Muslim families experience significant interactions and acculturation, particularly in the realm of marriage, which profoundly impacts theological aspects, including the concept of worshiping God, differing from the beliefs held by the Hindu community in the region. Muslim families hold a belief in one God, whereas the Hindu-Balinese community embraces the existence of multiple gods and goddesses, leading to various forms of worship. Muslim families in Bali enjoy the freedom to engage with other communities, primarily Hindu, just as Hindu families in Makassar do, reflecting the open nature of the people in both regions. Consequently, it will influence inclusive, moderate, and tolerant theology regarding religious differences.